Awareness Of Farmers In Using Personal Protective Equipment In The Event Of A Farmer Bitten By A Snake In Lumajang - Asih Pusparin; Prima Dewi Kusumawati (Journal of Hospital Management and Services, 2021)
One district in East Java where the majority of the population works as a farmer, namely in Lumajang district. Farmers need to use personal protective equipment when working to protect themselves from work accidents and hazardous materials used by farmers. This research focuses on farmers' awareness in terms of knowledge, attitudes and behavior of farmers in the use of personal protective equipment in Kaliwungu Village, Tempeh District, Lumajang. This type of research is descriptive research and uses qualitative methods. Using purposive sampling where there are 4 samples chosen are those who have been bitten by a snake. Data collection is done by means of interviews using interview guides that have been prepared.The results showed that farmers in Kaliwungu Village who had been bitten by a snake and did not use PPE when farming due to feeling uncomfortable and lack of self-motivation and family not to rule out the importance of using PPE to avoid being bitten by poisonous animals that threaten health and some PPE is not ergonomic when used.